2021
DOI: 10.1093/trstmh/traa180
|View full text |Cite
|
Sign up to set email alerts
|

Adapting an integrated neglected tropical disease programme in response to COVID-19

Abstract: The COVID-19 pandemic hit at a time when the Ascend West and Central Africa programme was nearing the end of its first year of a 3-y programme. This article reflects on key lessons learnt from the rapid adaptation of an integrated neglected tropical disease (NTD) programme to support COVID-19 responses in 11 countries. It shares the experiences of adopting a flexible and directive approach, leveraging the NTD network and relationships, and working in collaboration with multiple ministry departments, commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…As seen in both Guinea and Nigeria, albeit in the limited locations included in this study, NTD control programs can be successfully leveraged for the COVID-19 response and can enhance their own preparedness to future interruptions in so doing. Similar outcomes have also been observed in other countries in West and Central Africa [ 30 ]. More generally, these approaches provide opportunities for identifying further areas for activity or programmatic integration, either within the health system or through allied services such as WASH. Risk communication may be an area particularly ripe for closer integration between NTD programs and pandemic response.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As seen in both Guinea and Nigeria, albeit in the limited locations included in this study, NTD control programs can be successfully leveraged for the COVID-19 response and can enhance their own preparedness to future interruptions in so doing. Similar outcomes have also been observed in other countries in West and Central Africa [ 30 ]. More generally, these approaches provide opportunities for identifying further areas for activity or programmatic integration, either within the health system or through allied services such as WASH. Risk communication may be an area particularly ripe for closer integration between NTD programs and pandemic response.…”
Section: Resultssupporting
confidence: 89%
“…Continued forecasting will be a necessary tool to mitigate the impact of COVID-19 on future NTD programming [ 29 ]. Critically, ownership of these data must rest with the national NTD control programs and the Ministry of Health [ 30 ]. One option is for national governments to mandate that researchers and implementing partners focused on NTDs in endemic countries commit to providing the outcomes of their investigations and program evaluations to the national NTD control program.…”
Section: Resultsmentioning
confidence: 99%
“…A large mass media campaign initiated by Ascend reached 137 million people across 11 countries with COVID-19 risk mitigation messaging, generating much enthusiasm from programme and government partners alike. 4 In line with recent WHO guidance in the 2030 NTD road map, six countries (Benin, Cote d'Ivoire, DRC, Ghana, Guinea-Bissau and Nigeria) were supported in updating their new NTD master plans.…”
Section: Ascend West and Central Africa Programmementioning
confidence: 95%
“…Ascend was able to respond quickly and assisted national programmes in resuming activities by instituting a rapid rollout of mitigation measures against COVID-19. 4 …”
Section: Ascend West and Central Africa Programmementioning
confidence: 99%
“…The rapid adaptation of Ascend and other large-scale NTD programmes to the challenges of COVID-19 through innovation has shown that there are lessons to be learned from the remarkably agile adaptation of NTD programmes. 16 The pandemic will continue to present an opportunity to use innovation to advance integrated drug delivery mechanisms, recognising that new approaches are required to reach those most affected by NTDs, that is, low-income groups who are largely untargeted by private-sector health investment. 17 MoH's will need to lead the fight against NTDs through initiatives promoting the feasibility, desirability and scalability of innovative solutions.…”
Section: Key Lessons From the Fundmentioning
confidence: 99%